Application of Information Communication Technology to the Management of Library’s Readers’ Desk - Olaniyi, O.M.; Omotosho, A.; Oluwatosin, E.A.; Towolawi, O.K.; Grant-Ezeronye, G.C. (DESIDOC Journal of Library & Information Technology, 2012)
The automated library’s readers’ desk management system is a modern innovation that is expected to help in the circulation registration of processed books and register users. The existing library management system processes in most institutions of higher learning in the developing countries is not fast enough and it is mainly manually processed. This paper presents a library readers’ desk management system with the use of fingerprint biometric and barcode technology to the activities of a library’s readers’ services. The proposed system is capable of reducing the time spent and errors associated with identification and verification of users and library books as well as charging-in and charging-out of books to library patrons. http://dx.doi.org/10.14429/djlit.32.6.2849